Strengthening Fraud Prevention Through the Three Lines of Defense in Public Infrastructure Oversight - Dirgantara, Deka Bayu; Prastiwi, Arum; Rahmanti, Virginia Nur (Eduvest - Journal of Universal Studies, 2025)
This study examines the effectiveness of fraud prevention in the Directorate General of Infrastructure Financing at the Indonesian Ministry of Public Works using the Three Lines of Defense model. Employing a qualitative ethnomethodological approach, the research explores how actors in each line—the operational units, internal compliance, and internal auditors—perceive and perform their roles in everyday practices. Data were collected through in-depth interviews and focus group discussions with nine informants, representing each line equally. The analysis reveals that formal oversight structures are often interpreted and enacted through informal social norms, with coordination heavily reliant on interpersonal trust and ad hoc communication. The study identifies key challenges, including overlapping responsibilities, limited authority of the second line, and a lack of integrated procedures. Moreover, the findings highlight that the perception of fraud and internal control is shaped by collective social knowledge, which does not always align with institutional policies. This gap between formal frameworks and practical implementation undermines the overall effectiveness of fraud prevention mechanisms. The research suggests that aligning policy and practice requires developing cross-line standard operating procedures, empowering the second line structurally, fostering a culture of risk awareness, and institutionalizing collaborative forums to ensure coherent coordination. These strategies aim to reinforce not only structural integrity but also the social and cultural dimensions of internal oversight.